FILM AS MEDIA IS EMPOWERED DURING THE COVID 19 BY THE NDALEM AGENG PRODUCTION - Wiranto, Retnowati (Jurnal Abdimas Sang Buana, 2023)
The Ndalem Ageng Surakarta art community has experienced limited activity and movement since the Covid 19. This paper aims to provide ideas and motivate art workers, especially the Ndalem Ageng Production Community, Surakarta to continue working and growing in the new normal era through a local wisdom approach using the Javanese language and empowering artistic people as a way to empower and grow together through a film approach. The method used in this activity is participatory and directly involved in the Ndalem Ageng art community for a relatively long time so that they can really understand the issues, thoughts, behaviors and types of art owned by art workers who are members of the Ndalem Ageng community. The result of assisting the Ndalem Ageng art community is the realization of creative artistic activities through a film approach by combining the world of stage and film into a unique and interesting work. In conclusion, amid the new rules of behavior, the new normal post-covid-19, the Ndalem Ageng Surakarta art community, with different artistic backgrounds, can still continue their works of art by motivating one another and working together in film production. Efforts to establish networks through social media, meetings, discussions, offline sharing are carried out as a basis for mutual trust and mutual growth. In this new normal era, it has been proven that the Ndalem Ageng art community remains creative and works and is responsible for the processes being carried out.